Timing analysis: from predictions to certificates - Gaspar, Nuno Miguel Pires (2015)
In real-time systems timing properties must be satisfied in order to guarantee that deadlines will be met. In this context, the calculation of theworst-case execution time(WCET) is of paramount importance for schedulability analysis. However, this problem can be difficult if the underlying architecture possesses features like caches and pipelines. This thesis presents all the necessary steps for the safe and preciseWCET calculation. We focus ourselves in the use of static analysis-based methods, and in the ARMarchitecture as target platform. Moreover, in order to ensure the correctness of our calculation to a program consumer, we produce a certificate (or proof ) whose validity entails compliance with the calculated WCET. This evidence permits to locally validate the calculated WCET, avoiding the need of a blind confidence on the producer.